Pagelaran Wayang Kulit Sebagai Sarana Aktualisasi Pendidikan Nilai Kearifan Lokal Dalam Tradisi Rasulan Di Karanganyar - Warsono Warsono (Institut Seni Indonesia Yogyakarta, 2024)
Wayang kulit is one of Indonesia's cultural heritages that is becoming increasingly unfamiliar to many of today’s younger generation. The emergence of new entertainment forms via various social media platforms has made wayang seem distant and less accessible to the public. The influence of modern globalization, coupled with the sophistication of internet features, provides people with a variety of entertainment options, further distancing traditional arts like wayang kulit. Nevertheless, some communities continue to strive to preserve this cultural art form to ensure its survival. One example of such local wisdom is the annual tradition of Rosulan (village cleansing), which includes wayang kulit performances held in Dusun Sukosari, Kecamatan Jumantono, Kabupaten Karanganyar. This study uses a qualitative descriptive method with a phenomenological approach. Data were collected through intensive interviews with key informants, including residents of Dusun Sukosari, community leaders, and religious figures. Observations were conducted by examining the environment where the wayang performances were held. Documents such as committee arrangements and reports were also utilized, along with photographs of the wayang kulit performances for visual support. Informants were selected using purposive sampling techniques. Data analysis employed an interactive model consisting of data reduction, data presentation, and conclusion drawing or validation.This research aims to identify the factors influencing the continuity of the Rosulan tradition with its wayang kulit performances in Dusun Sukosari, explore the values of local wisdom embedded in this tradition that allow it to endure across generations, and discover strategies for preserving wayang kulit among younger generations. The study was conducted in Dusun Sukosari, Desa Sukosari, Kecamatan Jumantono, Kabupaten Karanganyar, with the research subjects being local residents and the audience of wayang kulit performances during Rosulan.